2008
DOI: 10.1099/ijs.0.65723-0
|View full text |Cite
|
Sign up to set email alerts
|

Shinella kummerowiae sp. nov., a symbiotic bacterium isolated from root nodules of the herbal legume Kummerowia stipulacea

Abstract: Bacterial strain CCBAU 25048 T was isolated from root nodules of Kummerowia stipulacea grown in Shandong province of China. Cells of the strain were Gram-negative, strictly aerobic, nonspore-forming, motile short rods. Phylogeny of 16S rRNA gene sequences revealed that the strain belonged to the genus Shinella, a member of family Rhizobiaceae. Its closest phylogenetic relatives were Shinella granuli Ch06 T and Shinella zoogloeoides IAM 12669 T , respectively showing 98.3 and 98.9 % 16S rRNA gene sequence simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 26 publications
(22 reference statements)
3
38
0
1
Order By: Relevance
“…Rhizobia currently consist of 98 species belonging to 13 different genera. The predominant symbionts for most legume species in habitats throughout the world are found in the a-class of Proteobacteria: Rhizobium, Azorhizobium, Ensifer (formerly Sinorhizobium), Mesorhizobium, Bradyrhizobium, Methylobacterium (Jaftha et al, 2002;Jourand et al, 2004), Devosia (Rivas et al, 2003), Shinella (Lin et al, 2008), Ochrobactrum (Trujillo et al, 2005;ZurdoPineiro et al, 2007), Phyllobacterium (Valverde et al, 2005;Mantelin et al, 2006) and Microvirga (Ardley et al, 2012). Moreover, about eight species within two genera of β-class of Proteobacteria -Burkholderia and Cupriavidus have been reported (Moulin et al, 2001;Chen et al, 2001;Klonowska et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rhizobia currently consist of 98 species belonging to 13 different genera. The predominant symbionts for most legume species in habitats throughout the world are found in the a-class of Proteobacteria: Rhizobium, Azorhizobium, Ensifer (formerly Sinorhizobium), Mesorhizobium, Bradyrhizobium, Methylobacterium (Jaftha et al, 2002;Jourand et al, 2004), Devosia (Rivas et al, 2003), Shinella (Lin et al, 2008), Ochrobactrum (Trujillo et al, 2005;ZurdoPineiro et al, 2007), Phyllobacterium (Valverde et al, 2005;Mantelin et al, 2006) and Microvirga (Ardley et al, 2012). Moreover, about eight species within two genera of β-class of Proteobacteria -Burkholderia and Cupriavidus have been reported (Moulin et al, 2001;Chen et al, 2001;Klonowska et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors found that bacteria of the genera Burkholderia (Moulin et al, 2001) and Cupriavidus (Ralstonia) (Chen et al, 2001;Vandamme & Conye, 2004), both belonging to the class β-proteobacteria are also able to fix N 2 and form nodules on legumes. Besides, other genera and families in Rhizobiales (α-proteobacteria) were described as N 2 -fixing bacteria able to establish symbiosis with legumes: Devosia (Rivas et al, 2002(Rivas et al, , 2003, Phyllobacterium (Valverde et al, 2005), Methylobacterium (Sy et al, 2001;Jourand et al, 2004), Ochrobactrum (Trujillo et al, 2005) and Shinella (Lin et al, 2008).…”
Section: Exopolysaccharides Producedmentioning
confidence: 99%
“…In the absence of positive nodulation tests, they can be regarded as non-rhizobial endophytes (NRE). These include i.a., Alphaproteobacteria (Aminobacter (Estrella et al, 2009), Ochrobactrum (Zurdo-Pineiro et al, 2007Imran et al, 2010), Methylobacterium (Palaniappan et al, 2010), Devosia (Bautista et al, 2010) and Phyllobacterium (Mantelin et al, 2006)), Betaproteobacteria (Herbaspirillum (Valverde et al, 2003) and Shinella (Lin et al, 2008)), Gammaproteobacteria (Pantoea, Enterobacter and Pseudomonas (Benhizia et al, 2004;Ibañez et al ., 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 R-40421, R-45534, R-45535, R-45537, R-45540, R-45543, 23,30,161,170,188,303,362,375,376,377,378,380,420,421,422,423,424,425,432,…”
Section: Introductionmentioning
confidence: 99%